2014
DOI: 10.1093/nar/gku656
|View full text |Cite
|
Sign up to set email alerts
|

5′ isomiR variation is of functional and evolutionary importance

Abstract: We have sequenced miRNA libraries from human embryonic, neural and foetal mesenchymal stem cells. We report that the majority of miRNA genes encode mature isomers that vary in size by one or more bases at the 3′ and/or 5′ end of the miRNA. Northern blotting for individual miRNAs showed that the proportions of isomiRs expressed by a single miRNA gene often differ between cell and tissue types. IsomiRs were readily co-immunoprecipitated with Argonaute proteins in vivo and were active in luciferase assays, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
214
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(227 citation statements)
references
References 37 publications
10
214
3
Order By: Relevance
“…Thus, miR-223 5 ′ -isomiR expression appears to broaden the overall range of miR-223 targets. The prediction that 5 ′ -isomiR expression can impact miRNA target ranges is further supported by the confirmation of small sets of differentially regulated targets for an aberrant miR-307 5 ′ -isomiR in flies (Fukunaga et al 2012) and for transfected 5 ′ -isomiRs of miR-133a, miR-101, and miR-9 (Humphreys et al 2012;Llorens et al 2013;Tan et al 2014). On the other hand, it has been suggested that 5 ′ -isomiRs have highly overlapping targets (Cloonan et al 2011;Llorens et al 2013) and could therefore act redundantly, to increase the effective miRNA dosage or reduce offtarget effects (Cloonan et al 2011).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Thus, miR-223 5 ′ -isomiR expression appears to broaden the overall range of miR-223 targets. The prediction that 5 ′ -isomiR expression can impact miRNA target ranges is further supported by the confirmation of small sets of differentially regulated targets for an aberrant miR-307 5 ′ -isomiR in flies (Fukunaga et al 2012) and for transfected 5 ′ -isomiRs of miR-133a, miR-101, and miR-9 (Humphreys et al 2012;Llorens et al 2013;Tan et al 2014). On the other hand, it has been suggested that 5 ′ -isomiRs have highly overlapping targets (Cloonan et al 2011;Llorens et al 2013) and could therefore act redundantly, to increase the effective miRNA dosage or reduce offtarget effects (Cloonan et al 2011).…”
Section: Introductionmentioning
confidence: 83%
“…These include whether 5 ′ -isomiR expression is regulated in specific tissues, at different developmental stages, or in disease. Instances of spatial and temporal variation in the relative expression of isomiRs (isomiR switching) have been described (Fukunaga et al 2012;Tan et al 2014). For instance, the relative expression of the convergent miR-101 and miR-101+1 isomiRs changes from 1:2 in the brain to 3:1 in fetal lung fibroblasts (Tan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is of profound importance for miRNA's function, because the addition or deletion of nucleotides at the isomiR 5 0 end results in a change in the seed region and, consequently, leads to the regulation of a distinct set of target genes compared to the isomiR's canonical counterpart. As functional partners of their reference canonical molecules, isomiRs are tissue specific; therefore, the proper interpretation of microRNA-regulated networks requires comprehensive information on the miRNome for each particular tissue type (15,16,17).…”
Section: Microrna Function and Biogenesismentioning
confidence: 99%